ER-resident CCDC134 safeguards TLR4 maturation by maintaining gp96 stability - Yang Bai; Chao Zhang; Hao Liu; Fan Deng; Zeyu Wu; Wanyan Deng; Zengzhang Zheng; Rui Min; Shenglin Mei; He Kang; Huiqing Yu; Youdong Pan; et al. (Proceedings of the National Academy of Sciences, 2025)
Toll-like receptor 4 (TLR4), a pattern-recognition receptor located on the plasma membrane, senses extracellular danger signals to initiate inflammatory immune responses. It is initially synthesized in the endoplasmic reticulum (ER), undergoes N-linked glycosylation, and is subsequently transported to the Golgi before ultimately reaching the plasma membrane. However, the mechanisms underlying the processing and maturation of TLR4 in the ER remain elusive. Through whole genome-wide CRISPR screening, CCDC134 was identified as a critical and essential factor for TLR4-dependent inflammatory response. Localization of CCDC134 in the ER lumen rather than its exosome-mediated secretion is required for its role in TLR4 signaling. Loss of CCDC134 results in the retention of TLR4 in the ER for subsequent ER-associated degradation, and thus blockade of TLR4 maturation and plasma membrane trafficking. Defects in TLR4 processing and maturation in the ER in CCDC134-depleted cells are caused by aberrant hyperglycosylation and destabilization of glycoprotein 96 (gp96), a key chaperone of TLR4. These results suggest that CCDC134 controls gp96 glycosylation to facilitate TLR4 maturation in the ER.